Caracterização do comportamento mecânico de uma blenda polimérica de poliestireno - Santos, Fabiano dos (2018)
The Polystyrene (PS) this is homopolymer material, in which it is formed by only one monomer, this monomer is the result of the polymerization of styrene. This context, the head main focus of this study is the mechanical and physical behavior polymer when mixed with other polymers of the same class. Whit the presence of the other type of polymer as aggregator in the formation of a polymer blend, may influence the orientation of the molecular chains and thereby alter the properties. The blend is the terminology adopted in the technical literature on polymers for representing physical mixtures of two or more polymers, so that between the molecular chains of different polymers there is only secondary intermolecular interaction or there is not a high degree of chemical reaction between the molecular chains of the polymers. A blend may change the properties of the material relative to the pure polymers and for this verification were performed between three PS types (500, 525 and 535) to measure the mechanical properties and flammable of the blends.